The Effect of Liquidity, Leverage, Profitability and Company Size on Stock Prices in Mining Companies Listed on the Indonesia Stock Exchange in the Period of 2013-2017 - Shelvia Angeline; Jessy Sitorus; Mustika Sumbayak; Sri Purba; David (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2020)
This research aims to specify the effect of liquidity, leverage, profitability and company size on the stock price of mining companies listed on the Indonesia Stock Exchange in the period of 2013-2017. This type of research is descriptive statistical research. The object of this research had been done on 26 mining companies listed on the Indonesia Stock Exchange that were collected by purposive sampling. The data type that used in this research is called secondary data in the configuration of mining company financial statements for the period 2013-2017. The ratios used during this research are Current Ratio representing Liquidity, Debt to Equity Ratio that represents Leverage, Return On Assets representing Profitability and LN (Total Assets) representing Company Size. The analysis used is descriptive analysis, graph analysis also multiple linear regression analysis. The conclusion showed that liquidity had a positive and significant effect on stock prices. Leverage has a negative and not significant effect on stock prices. Profitability has a positive and significant effect on stock prices. Company Size has a negative and significant effect on stock prices.